The Effect of Using Training Aids On Direct Free Kick Scoring Accuracy In Youth Football Players Aged 17 – 19 Years Old - Majeed, Sanaa; Hassan, Flah (Journal of Physical Education, 2017)
The importance of the research lies in direct free kick scoring in football and its effect on match results. The problem of the research lies in the lack of exercises that develop free kick scoring in football. The aims of the research lies in designing special exercises using training aids to develop the accuracy of free kick in youth football scoring as well as identifying the effect of these special exercises using training aids on the development of free kick accuracy in youth football. The researcher hypothesized the positive effect of special exercises on the development free kick accuracy in youth football. In addition to that he hypothesized differences between pre and posttests in free kick accuracy. The researcher used the experimental method. The subjects were (5) youth football players aged 17 – 19 years old from Al Zewraa club. The data was collected and treated using proper statistical operations to come up with the conclusions and recommendations. The researcher concluded that the special exercises have positive effects on the development of free kick accuracy and using training aids motivated players to attend all training sessions. Finally the researcher recommended the necessity of using these special exercises with training aids especially on players specialized in free kick